The Effectiveness of Biofilter With Used Plastic Media and Aquatic Plants (Echinodorus palaefoliu and Limmnocharis flava) to Reduce the TSS and Amonia in the Rubber Industry’s Liquid Waste - Halim, Abdul; Hasbi, M.; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Liquid waste from rubber industry is one of environmental issues that shall be handled as it is commonly discharged and potentially contaminate aquatic environment. This waste contain high organic materials and it need to be processed. To understand the effectiveness of combination of used plastic biofilter media and emergent aquatic plant for remediation of that waste, a study has been conducted from January to March 2015. The waste was processed through used plastic biofilter media and then flown to phytoremediation unit that was completed with Limmnocharis flava and Echinodorus palaefoliu. There were 2 sets of processor and each set contain a biofilter and a phytoremediation unit. The processed waste was then used to rear Cyprinus carpio, Pangasius pangasius and Oreochromis niloticus fingerlings, 20 fishes/ aquarium. Water samplings were conducted 3 times, once/ 2 weeks. The water was sampled from the inlet and in the outlets of each biofilter and phytoremediation unit. Survival rate of the fish by the end of the research was noted. Results shown that the use of used plastic biofilter media and emergent plant phytoremediation process was effective to reduce the organic pollutant. Before being treated, the TSS and Ammonia were 538 mg/L and 28 mg/L respectively. After being treated, the TSS reduced into 32 mg/L and the Ammonia reduced into 7 mg/L. The effectiveness of the processor was 94% for the TSS and 75% for the Ammonia. By the end of the research, survival rate of the fish was ranged from 90%- 100%. Based on data obtained, it can be concluded that the use of used plastic and emergent plant processor is effective for reducing organic materials in the rubber industry liquid waste.Keyword : Used plastic, Limmnocharis flava, Echinodorus palaefoliu, rubber industry liquid waste